The impact of COVID-19 lockdown on physical activity and sedentary behaviour in secondary school teachers: a prospective cohort study - Yanni Verhavert; Tom Deliens; Lara Stas; Elke Van Hoof; Benedicte Deforche; Dirk Aerenhouts; Peter Clarys; Evert Zinzen; Kristine De Martelaer (BMC, 2024)
Abstract Background Mid-March 2020, Belgium went in lockdown to combat the COVID-19-pandemic. Having to provide school-based day care and adapt to online teaching, while all social, cultural and sports events and activities were cancelled, secondary school teachers' physical activity (PA) and sedentary behaviour (SB) may have been affected considerably. This study investigates the impact of the first Belgian lockdown on PA and SB in Flemish secondary school teachers. Methods This prospective cohort study was conducted throughout the 2019-2020 school year. PA and SB measured in March/April 2020 were compared with a pre-lockdown measurement in January/February 2020. Other pre-lockdown measurements (September/October 2019 and November/December 2019) and one other during-lockdown measurement (May/June 2020) allowed us to control for confounding. Validated questionnaires were used to assess participants' PA and SB. Generalized linear mixed models were applied in R. Results Among 624 participants (77·2% females, 43·3 ± 10·3 years), increases were observed for total PA (+ 108 min/week; p = 0·047), moderate PA (+ 217 min/week; p = 0·001), domestic and garden PA (+ 308 min/week; p < 0·0001) and leisure-time PA (+ 131 min/week; p < 0·0001), whereas work-related PA (-289 min/week; p < 0·0001) and active transportation (-38 min/week; p =0·005) decreased. No differences were observed for walking (p = 1·0) and vigorous PA (p = 0·570). Increases were found for total SB (+ 972 min/week; p < 0·0001), work-related SB (+ 662 min/week; p < 0·0001) and leisure-time SB (+ 592 min/week; p = 0·0004), whereas transport-related SB (-290 min/week; p < 0·0001) decreased. Conclusion During the lockdown, we found in our sample that Flemish secondary school teachers showed an increase in SB that was 9 times as high as their PA increase. As a government, education network or school, it is crucial to sensitize, promote, and facilitate sufficient MVPA and/or walking, but likewise to discourage SB during pandemic-induced lockdowns.